Circularly polarized light emission and detection by chiral inorganic semiconductors - Zha Li; Wancai Li; Dehui Li; Wei Tang; Huageng Liang; Huaibing Song; Chao Chen; Liang Gao; Jiang Tang (Frontiers of Optoelectronics, 2024)
Abstract Chiral inorganic semiconductors with high dissymmetric factor are highly desirable, but it is generally difficult to induce chiral structure in inorganic semiconductors because of their structure rigidity and symmetry. In this study, we introduced chiral ZnO film as hard template to transfer chirality to CsPbBr3 film and PbS quantum dots (QDs) for circularly polarized light (CPL) emission and detection, respectively. The prepared CsPbBr3/ZnO thin film exhibited CPL emission at 520 nm and the PbS QDs/ZnO film realized CPL detection at 780 nm, featuring high dissymmetric factor up to around 0.4. The electron transition based mechanism is responsible for chirality transfer. Graphical Abstract